Analisis Berpikir Kritis Siswa yang Bergaya Kognitif pada Pembelajaran Biologi Melalui Model Pembelajaran Contextual Teaching And Learning (CTL) dengan Media Visual - Putri Astuty Riwayati; Imas Cintamulya (Universitas Sebelas Maret, 2017)
This study aims to describe the ability of critical thinking with cognitive style by applying Contextual Teaching and Learning (CTL) learning model with visual media on the subject of environmental pollution in Islamic Junior High School Alhuda Sedayulawas Lesson Year 2016/2017. The subjects of this study are the seventh grade students of Islamic Alhuda Islamic Junior High School as many as 26 students, consisting of 5 students of reflective cognitive style, 5 students of cognitive impulsive style, 8 students with cognitive style accurately and 8 students cognitively slow inaccurate. Data collection techniques are critical thinking tests on the subject of environmental pollution referring to the Ennis (1985) indicator, for cognitive style tests using the Matching Familiar Figures Test (MFFT) test referring to Warli (2010). Data critical thinking techniques used nonparametric statistical analysis with Mann Whitney test (mann-whitnet test), for cognitive style data analysis obtained by Matching Familiar Figures Test (MFFT) test. Based on the results of research that has been done shows that children who have accurate cognitive style accurate way of critical thinking is better than other cognitive-style children. The conclusion is that cognitive-style students are accurately better than other cognitive-style students on the subject of environmental pollution through Contextual Teaching and Learning (CTL) learning models with visual media.